Salicornia as a salt-tolerant crop: potential for addressing climate change challenges and sustainable agriculture development - Shambhu, Katel; Yadav, Shubh Pravat Singh; Turuyasingura, Benson; Mehta, Aman (Turkish Journal of Food and Agriculture Sciences, 2023)
Halophyte plant Salicornia has potential uses in farming and environmental management. Salicornia is one of the most important families of halophytes and known for its exceptional salt tolerance. It thrives well in saline habitats near coastal areas. A comprehensive review paper provides an overview of Salicornia, including details on the impact of temperature and salinity on the germination of different ecotypes, as well as the influence of day length and salinity on seedling establishment. Salicornia L. presents a promising opportunity for sustainable agriculture and economic development as it may improve the lives and livelihoods of underprivileged groups while also benefiting the environment through carbon sequestration, soil preservation, and biodiversity preservation.